First space encyclopedia - Bingham, Caroline, 1962- (London ; New York : DK, 2008)
Provides information about various aspects of space, explaining what it is, and discussing the origins of the solar system, space exploration, objects in the solar system, comets and meteors, space mysteries, stars and constellations, space technology, and other topics.
At head of title: DK.
Includes index.
6.4
3-6
Keywords: Astronomy -- Encyclopedias, Juvenile; Outer space -- Encyclopedias, Juvenile; Astronomy -- Encyclopedias; Outer space -- Encyclopedias; Astronomy -- Encyclopedias; Outer space -- Encyclopedias